PENGARUH KOMITE AUDIT, KOMISARIS INDEPENDEN, DAN REPUTASI AUDITOR TERHADAP NILAI PERUSAHAAN: NILAI PERUSAHAAN - Raufa Yasa Iznillah; Yunita Kurnia Shanti (Yayasan Kayyis Mulia Jaya, 2026)
This study aims to empirically demonstrate the influence of the audit committee, independent commissioners, and auditor reputation on firm value. This study uses associative quantitative research and uses secondary data in the form of annual financial reports published on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. The population in this study was 65 industrial sector companies for the 2020-2024 period. The sampling technique was purposive sampling, resulting in 14 companies or 70 observational data. Hypothesis testing used panel data regression analysis with a Random Effect Model. The F-test results indicate that the Audit Committee, Independent Commissioners, and Auditor Reputation have a significant simultaneous effect on Firm Value. The T-test results indicate that the Audit Committee has a significant negative effect on firm value. Meanwhile, independent commissioners and auditor reputation have no effect on firm value. Keywords: Audit Committee, Independent Commissioners, Auditor Reputation on Firm Value.